Alzheimer Disease Biomarkers and Driving in Clinically Normal Older Adults: Role of Spatial Navigation Abilities. (April 2018) - Allison, Samantha; Babulal, Ganesh M.; Stout, Sarah H.; Barco, Peggy P.; Carr, David B.; Fagan, Anne M.; Morris, John C.; Roe, Catherine M.; Head, Denise
Abstract : Purpose: Older adults experience impaired driving performance, and modify their driving habits, including limiting amount and spatial extent of travel. Alzheimer disease (AD)-related pathology, as well as spatial navigation difficulties, may influence driving performance and driving behaviors in clinically normal older adults. We examined whether AD biomarkers [cerebrospinal fluid (CSF) concentrations of Aβ42, tau, and ptau181 ] were associated with lower self-reported spatial navigation abilities, and whether navigation abilities mediated the relationship of AD biomarkers with driving performance and extent. Methods: Clinically normal older adults (n=112; aged 65+) completed an on-road driving test, the Santa Barbara Sense of Direction scale (self-report measure of spatial navigation ability), and the Driving Habits Questionnaire for an estimate of driving extent (composite of driving exposure and driving space). All participants had a lumbar puncture to obtain CSF. Results: CSF Aβ42, but not tau or ptau181, was associated with self-reported navigation ability. Lower self-reported navigation was associated with reduced driving extent, but not driving errors. Self-reported navigation mediated the relationship between CSF Aβ42 and driving extent. Conclusions: Findings suggest that cerebral amyloid deposition is associated with lower perceived ability to navigate the environment, which may lead older adults with AD pathology to limit their driving extent.